2010
DOI: 10.2308/acch.2010.24.1.25
|View full text |Cite
|
Sign up to set email alerts
|

CFO Gender and Accruals Quality

Abstract: SYNOPSIS: The authors examine the association between chief financial officer (hereafter, CFO) gender and the quality of accruals. Based on findings in prior research on gender differences in a variety of decision settings—risk-taking attitudes, financial judgments, and regulatory compliances—they hypothesize that firms with female CFOs will have higher quality of accruals. The empirical findings, based on a sample of 1,559 (1,222) firms in 2005 (2004), support this hypothesis. The study shows that companies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
306
3
21

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(373 citation statements)
references
References 37 publications
43
306
3
21
Order By: Relevance
“…This implies that the female participation exhibit higher level of accounting conservatism. This findings support the results in several previous studies (e.g., Barua et al, 2010;Peni & Vä hä maa, 2010;Ho et al, 2015), which indicate that women involvement on boards enhance board monitoring, because the female directors are more ethical and risk averse, tend to report more conservative earnings and they have the ability to recognize bad news in reported earnings in a more timely fashion. This result is consistent with Ginesti et al (2018), who found that the existence a considerable proportion of female directors on the board gives more quality and transparency for financial statements.…”
Section: Multivariate Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…This implies that the female participation exhibit higher level of accounting conservatism. This findings support the results in several previous studies (e.g., Barua et al, 2010;Peni & Vä hä maa, 2010;Ho et al, 2015), which indicate that women involvement on boards enhance board monitoring, because the female directors are more ethical and risk averse, tend to report more conservative earnings and they have the ability to recognize bad news in reported earnings in a more timely fashion. This result is consistent with Ginesti et al (2018), who found that the existence a considerable proportion of female directors on the board gives more quality and transparency for financial statements.…”
Section: Multivariate Analysissupporting
confidence: 91%
“…For example, (e.g., Barua et al, 2010;Peni & Vä hä maa, 2010;Francis et al, 2015) pointed out that companies with women CFO have lower absolute discretionary accruals or higher income-decreasing discretionary accruals. Based on a sample of 435 Italian firms for the years 2009 to 2013, Ginesti et al (2018) found that the presence of female on the board have a positive effect on disclosure process and annual reports' transparency.…”
Section: Gender Diversity and Accounting Conservatismmentioning
confidence: 99%
“…Although a significant amount of accounting research has been devoted to testing the association between the effectiveness of corporate governance and audit committees on earnings management (Lin and Hwang 2010;Benkraiem 2009;Ebrahim 2007;Xie et al 2003;Klein 2002), only a few studies have examined the association between gender diversity on the board of directors and earnings management. For instance, Barua et al (2011) investigated the association between CFO gender and earnings management and found that firms with female CFOs have lower discretionary accruals than firms with male CFOs. Similar findings were provided by Peni and Vähämaa (2010), who examined the association between CFO and CEO gender and earnings management, and found that firms with female CFOs have income-decreasing discretionary accruals, indicating that female CFOs are following more conservative financial reporting rules and standards.…”
Section: Female Directors and Earnings Management -The Key Questionsmentioning
confidence: 99%
“…The magnitude of accruals and the likelihood of beating analysts' forecasts are more sensitive to CFO equity incentives than to those of the CEO Barua et al (2010) Chief During the recession, the presence of more powerful CFOs is associated with larger audit fee reductions, and the presence of a more powerful audit committee is associated with lower audit fee reductions Bird et al (2008) Chief Counsel (also known as Chief Legal Officer or General Counsel)…”
Section: Introductionmentioning
confidence: 99%